Hypervolemic Hyponatremia as a Reversible Cause of Cardiopulmonary Arrest in a Postpartum Patient with Preeclampsia - Richard Hsu; Anna Tong; Chaur-Dong Hsu (Case Reports in Obstetrics and Gynecology)
Although the incidence of preeclampsia complicated by hyponatremia is reportedly rare, the effects on the maternal outcome are severe and life-threatening. Here, we describe a case of a patient with preeclampsia who coded postpartum and was discovered to have hypervolemic hyponatremia and subsequently recovered after fluid diuresis and resolution of hyponatremia. While hyponatremia in preeclampsia is rare, it is even more unique for it to lead to cardiopulmonary arrest consequently. Therefore, sodium levels and fluid status should be monitored closely and promptly corrected without delay to prevent cardiopulmonary arrest in patients with preeclampsia.